Michał Kaziów: the Way to Independence of the Blind Writer in the Context of Selected Issues of Narrative Medicine and Human Rights - Bolińska, Marta; Zieliński, Patryk (Respectus Philologicus, 2021)
The article undertakes constructive reflection on the loss of human health in the context of the issue of disability, with an indication that it is a state of mind rather than actual, physical impotence. The main subject of considerations is the attitude of the writer, Michał Kaziów, perceived as a way to independence and creativity developed as a result of his health condition in the light of selected issues of narrative medicine and human rights. The paper presents the difficult fate of Kaziów after a permanent loss of fitness (L. Kowalewski, M. Czerwińska) under the model of social disability (P. Hunt, M. Oliver) and an autobiographical attitude (M. Czermińska). The views of R. Charon (a doctor and a literary scholar) and her co-workers were also taken into account, according to which narrative medicine is a specific, well thought and described in the literature on the subject form of clinical (and didactic) practice that supports the process of diagnosis and treatment. Simultaneously, a review of laws and regulations on the creation of legal norms that supported people with disabilities and their evolution was undertaken. The whole text correlates with the thesis that the change in approach to disability is a living testimony to overcoming difficulties and their consequences, both in an individual and collective experience.